THE COMMUNITY POTENTIALLY IN ECOTOURISM MANAGEMENT IN THAKHA DISTRICT SAMUTSONGKHRAM PROVINCE - Jiranee Phanmool; Varothai Sommit; Anusorn Saechan (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2019)
The purposes of this research were: 1) to study the tourism management potential of the community and 2) to find out the method in order to develop the ecotourism management of Thaka Community, Amphawa District, Samut Songkhram Province. The mixed method of qualitative and quantitative research methodologies were used for collecting the data in this research. The qualitative data were collected from key informants by using in-depth interview and group discussion. The quantitative data were collected from the sample of tourists and community members. The finding revealed that the community has the potential of area resources management at highest level since the community has its long time history, unique way of life, outstanding traditions and wisdoms, and natural area which approach for the management. According with the evaluation on the potential of the community, the community has the high potential about area resources. The result from the opinion of the community member sample group was at mean score of 3.60, and the result from the opinion of the tourist sample group was at mean score of 3.87. The methods to develop the community tourism management were as follows: 1) increase the awareness of the community members to love their community and cherish its possessions, 2) encourage community members to participate with the management of the community, 3) develop the knowledge of community members about tourism management, 4) develop the existing tourist destinations into the ecotourism destinations, 5) develop the community tourism networks, and 6) publicize tourism destinations of the community.